T-cell-mediated cross-strain protective immunity elicited by prime–boost vaccination with a live attenuated influenza vaccine - Junwei Li; Maria T. Arévalo; Yanping Chen; Shan Chen; Mingtao Zeng (International Journal of Infectious Diseases, 2014)
Background: Antigenic drift and shift of influenza viruses require frequent reformulation of influenza vaccines. In addition, seasonal influenza vaccines are often mismatched to the epidemic influenza strains. This stresses the need for a universal influenza vaccine. Methods: BALB/c mice were vaccinated with the trivalent live attenuated (LAIV; FluMist) or inactivated (TIV; FluZone) influenza vaccines and challenged with PR8 (H1N1), FM/47 (H1N1), or HK/68 (H3N2) influenza virus. Cytokines and antibody responses were tested by ELISA. Furthermore, different LAIV dosages were applied in BALB/c mice. LAIV vaccinated mice were also depleted of T-cells and challenged with PR8 virus. Results: LAIV induced significant protection against challenge with the non-vaccine strain PR8 influenza virus. Furthermore, protective immunity against PR8 was dose-dependent. Of note, interleukin 2 and interferon gamma cytokine secretion in the lung alveolar fluid were significantly elevated in mice vaccinated with LAIV. Moreover, T-cell depletion of LAIV vaccinated mice compromised protection, indicating that T-cell-mediated immunity is required. In contrast, passive transfer of sera from mice vaccinated with LAIV into naïve mice failed to protect against PR8 challenge. Neutralization assays in vitro confirmed that LAIV did not induce cross-strain neutralizing antibodies against PR8 virus. Finally, we showed that three doses of LAIV also provided protection against challenge with two additional heterologous viruses, FM/47 and HK/68. Conclusions: These results support the potential use of the LAIV as a universal influenza vaccine under a prime–boost vaccination regimen.